The Effect of an Educational Curriculum Used the Computer in Learning Some Basic Skills on the Weight Beam for Female Students in Artistic Gymnastics - Asad Khudhair Abbas; Ahmed Akram Mahmoud; Ferdous Majeed Ameen; Iesan Yousif Tawfiq (Eximia, 2025)
The research aims to identify the effect of a computer-based educational curriculum on learning fundamental skills on the balance beam and to determine the most effective group in learning these skills. The researchers have hypothesized that the educational curriculum using the computer has a positive effect on learning some basic skills on the balance beam apparatus for the experimental group. The research sample included second-year female students of the College of Physical Education and Sports Science- University of Diyala. The experiment was carried out during (15/10/2023 – 1/2/2024) in the gymnasium hall and computer laboratory in the College of Physical Education and Sports Science. The researchers prepared a special learning curriculum for the experiment using a computer to learn the skills under study in terms of technical and cognitive performances. This was needed for six weeks from (22/10/2023 to 12/12/2023) during conducting the main experiment. In comparison, post-tests were conducted after completing the educational curriculum for all skills. The researchers have concluded that the use of a computer helps in understanding and comprehending the detailed parts of the skill (technical performance) better than without using the computer during learning skill.